(untitled) (New York, NY, 2002)
As with the first edition, the purpose of the book is to present a synthesis of ideas and professional experience to address the complex area of environmental assessment. In keeping with the approach outlined in federal law -- NEPA -- and its implementing regulations, the book provides a comprehensive, systematic approach to analyzing the effect that a project or action may have on the human environment.
Keywords: Environmental impact analysis,Environmental policy; United states,United states